APPROACHES AND STRATEGIES FOR ISLAMIC RELIGIOUS EDUCATION LEARNING IN THE CONTEXT OF MERDEKA BELAJAR KAMPUS MERDEKA - Nurjana Cyntia Rahman; Burhanuddin Abdul Karim Mantau; Yanty K. Manoppo (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2026)
This article examines the implementation of Islamic Religious Education (PAI) learning approaches and strategies within the policy framework of Merdeka Belajar Kampus Merdeka (MBKM), or Independent Learning–Independent Campus. PAI learning within the MBKM framework emphasizes flexibility, authentic learning experiences, and student autonomy through humanistic, constructivist, experiential, and value-based approaches. These approaches strengthen character formation, value internalization, and the development of students’ reflective capacity. Furthermore, project-based learning, project-collaborative learning, problem-based learning, and blended learning strategies enable students to apply Islamic values in real-life contexts through projects, interdisciplinary collaboration, problem solving, and digital technology. Overall, PAI learning in MBKM becomes more contextual, applicable, and relevant to the needs of modern society. The implication of this study is that PAI learning in higher education needs to be designed more adaptively, collaboratively, and practically so that Islamic values are not only understood conceptually but also internalized and implemented in students’ academic, social, and professional lives. Therefore, this article highlights the importance of adaptive curriculum design, lecturers’ roles as facilitators, and collaboration with external partners in optimizing the implementation of PAI within the MBKM framework. The impact of implementing Islamic Religious Education (PAI) learning approaches and strategies within the MBKM framework is increased student engagement and independence in the learning process, the development of critical thinking, collaboration, and problem-solving skills, and the strengthening of the internalization and application of Islamic values ??in academic, social, and professional life. PAI learning also becomes more contextual, applicable, and relevant to the needs of society and the workplace.